Chemical Composition of the Essential Oil Extracted from the Tender Leg of Asparagus Acutifolius L. from two Different Regions in Lattakia – Syria - أردلان نعمان; حويجة عماد; عفيفة عيسى (Latakia University Journal -Basic Sciences Series, 2023)
Samples were collected from the tender leg branches of Asparagus acutifolius (genus Asparagus, Liliaceae) from two different areas in Lattakia: Al-Haffah(410m), Sanjuan(75m), and the essential oil was extracted from them by Hydrodistillation using the Cleveger apparatus, where the weight percentage of essential oil stood at 0.68%and 0.30% for both mountainous and coastal region ,respectively. Chemical composition of essential oil obtained from the tender leg branches of Asparagus acutifolius L. was analyzed by Gas Chromatography-Mass Spectrometer GC/MS . The results of the analysis of the essential oil of Al-Haffah region showed 15 compounds, which constituted 99.96%of the total chemical composition of the essential oil. The results of the analysis of the essential oil of Senjuan region showed 24 compounds, which constituted 99.91% of the total chemical composition of the essential oil, and it was found that the component with the highest percentage in both samples is Thiophene, which amounted to 97.36% in the tender leg of the Al-Haffah region and 71.7% in the tender leg of the Senjuan region.